The digital economy and international taxation: a literature review in a post-crisis context - LACHHAB, Mohamed; EL HADDAD, Mohamed Yassine; ABIZA, Oumnia (Revue Internationale des Sciences de Gestion, 2022)
Today’s new paradigm has shown that the digital economy is no more one of the economy’s areas but is shifting and becoming a vehicle for change of all the economy’s sectors eroding residence countries’ tax bases or creating double taxation on foreign digital companies. The digitization of the economy through the internet, cloud computing, big data, fintech and other new technologies that allow the use, the collection and the analysis of data as well as information sharing are driving numerous states to adopt new tax rules that would ensure that digital companies contribute equally to public finances. The new tax rules aim at changing how profits are allocated in a way which better reflects how digital companies generate value remotely, depending on where the custumers are based, for instance. This article intends to help understand the importance of an international taxation consensus regarding the way of creating an international framework for fair tax principles. Also, this review tries to highlight the meaningful contributions to a thorny subject such as taxation debate. Especially on how legislative proposals were implemented and how solutions were embraced to address tax challenges related to the digital economy.